Penggunaan Dialek Masyarakat Dusun Malangan Pademawu Timur Pamekasan - Kusyairi, Kusyairi; Maftuhah, Faradila Wahyu (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2019)
The preservation of language is in the Malangan hamlet community of Pademawu sub-district which has a characteristic in Madurese language. The village of Malangan is indeed known for its special characteristics in language. Although they still use Madura, the intonation and vocabulary they use have their own characteristics. Different intonation and duration with other regions. So that the area has its own characteristics in dialogue. This study aims: to describe objectively the use of the Malangan hamlet dialect in the fields; (1) intonation and (2) vocabulary. The formulation of the problem in this study is how the form of dialect usage in the Malangan village of Pademawu Timur. The approach in this research is a qualitative approach. The data in this study are sentences in conversation. The data source in this study is the Malangan hamlet community. Data collection techniques using the record technique. Contextual data analysis is performed by means of identification, classification, description and interpretation techniques. The results of this study indicate the use of the dialect of the East Malangan Pademawu hamlet community including intonation, and vocabulary. From the results of data analysis, it can be concluded that the dialect of East Pademawu hamlet community has its own characteristics in interacting. The use of intonation is low and is extended to the last syllable, so that it becomes a distinctive characteristic for the people of Malangan, East Pademawu. The vocabulary that is owned is also rich and varied so that there are some words that are used slightly differently from those used by the Pademawu community in general.